The Effect Of Brand Experience Toward Brand Loyalty Through Brand Satisfaction As A Mediating Variable (Study On Iphone Users In Indonesia) - Ahmad, Habib Nur; Basalamah, Muhammad Ridwan; Hardaningtyas, Ratna Tri (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to examine the relationship between brand experience and brand loyalty with brand satisfaction as a mediation variable. This research using i quantitative explanatory approach. The sample size was determined using the Slovin formula with a 10% margin of error, resulting in 100 respondents. Data analysis was conducted using the partial least squares. The stages of statistical analysis included tests for convergent and discriminant validity, reliability, and hypothesis testing. All statistical analyses were performed using SmartPLS 4 software. Research findings indicate that brand experience significantly and positively influences brand loyalty. Additionally, brand experience has a positive and significant effect on brand satisfaction. Brand satisfaction also positively and significantly impacts brand loyalty. Moreover, brand experience significantly affects brand loyalty when mediated by brand satisfaction. Keywords: Brand Experience. Brand Satisfaction, Brand Loyalty, iPhone